PENGEMBANGAN VIDEO DAN LEMBAR KERJA PESERTA DIDIK UNTUK TOPIK SISTEM PERSAMAAN LINEAR DUA VARIABEL KELAS VIII SMP - ALDI SAPUTRA (Jurnal Edukasi dan Penelitian Matematika, 2021)
Because of Corona Virus Disease (COVID-19), learning process is carried out in a network. So, it is necessary to innovate the deve1opment of technology-based student worksheet. This research airns to deve1op a video and Student Worksheets on the material of two-variable system of linear equations for class eighth junior high school students  which is va1id. This deve1oprnent research uses the Plornp developrnent mode1 which consists of three phases, name1y the Prelirninary research phase, the Prototyping phase, and the Assessrnent phase. Validation is carried out by mathernatics education experts and the practica1ity of Student Worksheets is seen from the practicality questionnaire results of the student response questionnaire which has heterogeneous abilities. Video and Student Worksheets is validity in terms of format, content eligibility, 1anguage, and learning activities with a validity level of 92,8% (very valid). Based on these results, it can be concluded that the video and Student Worksheets for class eighth junior high school students of two-variable system of linear equations material that has been produced can be dec1ared va1id. Keywords __ Development Research, Student Worksheet, Video, Two-Variable System of Linear Equations